The Isolation of Streptomyces species in Different Soil Sources from Middle Anatolian Regions of Turkey - Zeynep YİLMAZER HİTİT; Sila ELDEMİR; Harun BÜYÜKEĞEN; Kemal KESENCİ; Suna ERTUNÇ; Bülent AKAY (Journal of the Turkish Chemical Society Section B: Chemical Engineering, 2022)
Streptomyces is the largest species of the actinomycetes group, with more than 500 defined species, aerobic, gram-positive, and phylogenetic class filamentous (thin protruding in thread form). It is a large group that is mostly found in the soil and as a secondary metabolite of its fermentation, it enables the production of various and important components (antibiotics, chemotherapeutics, fungicides, herbicides, and immunosuppressants) in the field of industry and medicine. In this study, six bacterial isolates were isolated from soil samples in different regions of Turkey. Morphological characteristics, gram staining, and PCR test were applied for identification. Six isolates, Streptomyces mutabilis, S. collinus, S. peucetius, S. cyaneofuscatus, S. albogriseolus and, S. griseoflavus, were compared with the general characteristics of the Streptomyces species in International Streptomyces Project. Air and reverse side mycelium color were determined, and all were confirmed by the gram-positive test. Studies have shown that the regions of Ankara and Konya are rich in Streptomyces species.